Evaluating innovation adoption attribute in technology transfer - Juhaini, Jabar; Soosay, Claudine (2010)
This paper explores the impact of technology transfer on innovative capabilities and organisational performance in Malaysian manufacturers based on a survey of 335 Malaysian manufacturing organisations forming strategic technology alliances (STAs) to acquire external technologies. Established from the Diffusion of Innovations (DoI) theory, three innovation adoption attributes were utilised to form a structural equation model. The findings suggest that external technology acquisition alone is insufficient to sustain the long-term organisational performance and innovative capabilities in the Malaysian manufacturing industry. Recommendations are made for such organisations to develop their internal R&D and innovative capabilities so as to reap continued performance outcomes.